Are Women-Targeted Programs Women-Positive? - Jane Castle; Gillian Attwood; Suzanne Smythe (Adult Education Research Conference, 2001)
The authors distinguish between women-targeted and women-positive programs, citing examples of unsuccessful education programs in South Africa that were targeted at women. They question the educational and political aims of these initiatives and suggest that women-positive programs foreground gender within a broader context of transformation involving both men and women.